PERAN MEDIASI PENGUNGKAPAN LINGKUNGAN PADA PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Fransiskus Eduardus DAROMES (Jurnal Akuntansi, 2020)
The purpose of this study is to examine the effect of environmental performance on firm value both directly and through environmental disclosure. Population used is the whole company listed in Indonesia Stock Exchange period 2014-2018. Number of samples are 10 firms each year, were selected by purposive sampling method and using secondary data, i.e. the annual report, PROPER and sustainability report. The analytical methods used are path analysis and hypotesis mediation analysed by using sobel test. Statistical test shows that environmental performance has positive and significant effect on environmental disclosure. Environmental performance and environmental disclosure have positive and significant effect on firm value. This research also shows environmental disclosure mediates the effect of environmental performance on firm value